Early-Onset Hypertension – Clinical characteristics and relation to adverse outcomes - Suvila, Karri (fi=Turun yliopisto|en=University of Turku|, 2021)
ABSTRACT Established hypertension is a well-known risk factor for cardiovascular disease and dementia. However, limited evidence exists on the relation between the age of hypertension onset and adverse events. The aim of this thesis was to study the impact of early-onset hypertension on end-organ damage and cognitive function in midlife. Additional aims were to examine risk factors for early-onset hypertension and the feasibility of different methods for detecting hypertension onset age. This thesis is based on the Coronary Artery Risk Development in Young Adults (CARDIA), which is a biracial prospective follow-up study. The CARDIA study was initiated in 1985–1986 and included a sample of 5115 American young adults. The study participants underwent up to 30 years of follow-up with regularly conducted follow-up exams. We also included a separate study sample from the Health 2000 survey, a population-based study carried out in 2000–2001 that examined 8028 Finns. Both study samples collected either objective or self-reported data on the participants’ age of hypertension onset as well as an assessment of adverse outcomes. In the CARDIA study sample, we observed that an early age of hypertension onset was most robustly associated with echocardiographic left ventricular hypertrophy (LVH), diastolic dysfunction, and coronary calcification in midlife. Additionally, early-onset hypertension in these individuals was related to midlife cognitive impairment. In contrast, late-onset hypertension was not associated with these adverse outcomes. Self-reported hypertension onset age was not related to electrocardiographic LVH in the Health 2000 study sample. However, self-reported early-onset hypertension was associated with end-organ damage in the CARDIA participants. We also identified African American ethnicity, diabetes, and obesity as the most potent correlates of early-onset hypertension. In conclusion, early-onset hypertension, but not late-onset hypertension, is associated with having end-organ damage by midlife. Our findings demonstrate the importance of assessing the age of hypertension onset, even by patients’ self-report, in order to feasibly assess the lifetime burden of hypertension and to improve risk stratification of individuals with hypertension in clinical practice. TIIVISTELMÄ Verenpainetauti on merkittävä dementian sekä sydän- ja verisuonisairauksien riskitekijä. Aiempia tutkimuksia verenpainetaudin puhkeamisiän merkityksestä haittatapahtumien kehittymiselle on kuitenkin vähän. Tämän väitöskirjatutkimuksen tavoitteena oli tutkia varhain puhkeavan verenpainetaudin vaikutusta pääteelinvaurioihin sekä kognitiiviseen suorituskykyyn keski-iässä. Lisäksi selvitimme varhain puhkeavalle verenpainetaudille altistavia tekijöitä sekä eri menetelmien soveltuvuutta verenpainetaudin puhkeamisiän arvioimiseksi. Tutkimusaineistona käytettiin ensisijaisesti yhdysvaltalaista prospektiivista CARDIA-seurantatutkimusta, johon osallistui 5115 nuorta amerikkalaista miestä ja naista vuosina 1985–1986. Tutkimushenkilöt ovat osallistuneet 30 vuoden ajan säännöllisesti suoritettuihin seurantatutkimuksiin. Toinen tutkimusväestö koostui 8028 väestörekisteristä satunnaisotannalla valitusta suomalaisesta, jotka osallistuivat Terveys 2000-tutkimukseen vuosina 2000–2001. Molempien tutkimusotoksien osallistujilta määritettiin verenpainetaudin puhkeamisikä joko objektiivisesti tai itseilmoitettuna sekä mitattiin verenpainetaudin pääte-elintapahtumia. Ensimmäisessä tutkimusaineistossa varhaisella iällä puhjennut verenpainetauti oli voimakkaimmin yhteydessä vasemman kammion hypertrofiaan, sydämen diastoliseen toimintahäiriöön sekä sepelvaltimoiden kalkkeutumiseen keski-iässä. Varhainen verenpainetauti altisti myös kognitiivisten toimintojen heikentymiselle. Myöhäinen verenpainetauti ei ollut yhteydessä vastaaviin haittatapahtumiin. Myös itseilmoitettu varhain puhjennut verenpainetauti oli yhteydessä pääte-elinvaurioihin ensimmäisessä tutkimusotoksessa, mutta ei elektrokardiografisesti määritettyyn vasemman kammion hypertrofiaan toisessa tutkimusotoksessa. Afroamerikkalainen syntyperä, diabetes ja ylipaino olivat riskitekijöitä varhaiselle verenpainetaudille. Löydökset osoittavat, että erityisesti varhain puhkeava verenpainetauti altistaa verenpainetaudin pääte-elinvaurioille jo keski-iässä. Verenpainetaudin alkamisiän määrittäminen osana verenpainetaudin hoitoa voisi edesauttaa lääkäreitä huomioimaan korkean verenpaineen elinikäistä vaikutusta elimistöön ja mahdollisesti edistää näiden potilaiden tulevien haittatapahtumien ennaltaehkäisyä.